2017
DOI: 10.4025/actascibiolsci.v39i2.34082
|View full text |Cite
|
Sign up to set email alerts
|

<b>Cytotoxic and genotoxic effects of <i>Solanum lycocarpum </i> St.-Hil (Solanaceae) on the cell cycle of <i>Lactuca sativa</i> and <i>Allium cepa

Abstract: Solanum lycocarpum St.-Hil popularly known as 'fruta-de-lobo' or 'lobeira' is native to the Brazilian Cerrado, and used in folk medicine due to its phytotherapic properties. The action of S. lycocarpum on the cell cycle and chromosomes in order to demonstrate whether there are aneugenic and/or clastogenic effects is unknown. Thus, this study aimed at investigating the cytotoxic and genotoxic potential of methanol and hexane extracts of S. lycocarpum on growth and cell cycle of Lactuca sativa and Allium cepa. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…Por outro lado, os eventos clastogênicos causam a quebra cromossômica, formando pontes e aderência cromossômicas. A quebra de segmentos de cromossomos pode ocasionar a fusão inter ou intracromatínica, gerando formas irreversíveis de aderência ou levando a morte celular (CHIAVEGATTO et. al, 2017).…”
Section: Methodsunclassified
“…Por outro lado, os eventos clastogênicos causam a quebra cromossômica, formando pontes e aderência cromossômicas. A quebra de segmentos de cromossomos pode ocasionar a fusão inter ou intracromatínica, gerando formas irreversíveis de aderência ou levando a morte celular (CHIAVEGATTO et. al, 2017).…”
Section: Methodsunclassified
“…This species is widely used in folk medicine as a sedative, in the treatment of epilepsy, diabetes, obesity, reduction of cholesterol levels, and in the preparation of influenza syrups (Dall'Agno & Von Poser, 2000). Previous studies have shown that fruits of S. lycocarpum exhibit allelopathic, anti-inflammatory, antimicrobial, antioxidant, antitumoral, cytotoxic, genotoxic and larvicidal activities (Morais, Silva, Oliveira, Ferreira, & Lima, 2013;Pereira, Silva, Ribeiro Neto, Alves, & Lima, 2014;Morais et al, 2015;Silva, Ribeiro Neto, Alves, & Lima, 2015;Chiavegatto, Chaves, Silva, Lima, & Techio, 2017;Morais et al, 2017;Bahia et al, 2018;Morais et al, 2018;Silva et al, 2018;Silva, Fonseca, Coimbra, Duarte-Almeida, & Lima, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Vernonanthura polyanthes (assa-peixe) e observaram efeitos tóxicos da espécie em concentrações superiores a 20 mg/ml Chiavegatto et al (2017). relataram que os extratos metanolicos do fruto da Solanum lycocarpum (lobeira) têm um efeito inibitório sobre o crescimento das raízes tanto da A. cepa quanto da Lactuca sativa.…”
unclassified